Accuracy study of a novel alternate method measuring erythrocyte sedimentation rate for prototype hematology analyzer Celltac α+. (30th April 2021) - Maki, Ryosuke; Tabe, Yoko; Yamamoto, Takamasa; Takemura, Hiroyuki; Sawada, Tomohiro; Esaki, Tatsuhiro; Higuchi, Makoto; Misawa, Shigeki; Miyake, Kazunori; Miida, Takashi; Nagai, Yutaka; Ohsaka, Akimichi
Abstract: Introduction: The erythrocyte sedimentation rate (ESR) is a nonspecific inflammation indicator. In laboratory testing, automated ESR analyzers may use the reference Westergren method (Reference WG), modified Westergren (Modified WG), or Alternate ESR method (Alternate ESR) based on photometric rheology. A prototype hematology analyzer Celltac α+ (Nihon Kohden Corporation) with built‐in Novel ESR analysis technology (Novel ESR) was developed to improve the accuracy of Alternate ESR. Alternate ESR uses only the aggregation phase information of Reference WG. The Novel ESR adds sedimentation and packing phase information obtained by hematology analyzer measurands. High correlation with WG was ensured by predicting the ESR value using Hematocrit (Hct) and MCV values as correcting parameters. Methods: Novel ESR was compared with Modified WG (MONITOR‐40, Joko Corporation) and Reference WG, according to internationally recognized guidelines: Precision, carryover, limit of quantification, comparability, linearity, accuracy, and fibrinogen sensitivity. Samples from healthy volunteers and clinical patients were used. The correction performance of Novel ESR and Modified WG was compared with Reference WG by regression analysis in three range categories for ESR and measurands affecting ESR correction (Hct, MCV, and MCH). Results: Novel ESR showed sufficient basic performance and comparability with Modified WG. In the accuracy study comparing with Reference WG, the regression equation was y = 1.026x + 0.5( r  =  .945, P  <  .001;n = 271). When evaluating the correction performance, the slopes were within 0.8‐1.2, except for the high part of Hct. All intercepts were within 10 mm. Conclusion: This study validated the correction performance to the initial estimated ESR value by aggregation phase information using information reflecting sedimentation and packing phase obtained from automated hematology analyzer. The Celltac α+ Novel ESR provided results equivalent to Reference WG.